Anionic oxoborane and thioxoborane molecules supported by a 1, 2-bis(imino)acenaphthene ligand. Issue 20 (18th May 2021) - Liu, Rui; Gao, Fangfang; Liu, Jingjing; Wei, Jing; Hou, Lei; Xie, Gang; Chen, Sanping; Zeng, Fanlong; Li, Anyang; Wang, Wenyuan
Abstract : The isolable anionic oxoborane and thioxoborane, supported by a Dip-BIAN ligand, contain terminal doubly bonded BE (E = O, S) groups, respectively, in which only the BO group interacts with imidazolium via a hydrogen bond. Abstract : The isolable anionic oxoborane 3 and thioxoborane 4 have been assembled using a 1, 2-bis(imino)acenaphthene ligand (Dip-BIAN). Structural characterization and DFT calculations confirmed that two compounds contain terminal doubly bonded BE (E = O, S) groups, respectively, in which only the BO group is associated with imidazolium via a hydrogen bond.